Development of an in vitro Model of Human Gut Microbiota for Screening the Reciprocal Interactions With Antibiotics, Drugs, and Xenobiotics - El Houari, Abdelaziz; Ecale, Florine; Mercier, Anne; Crapart, Stéphanie; Laparre, Jérôme; Soulard, Baptiste; Ramnath, Manilduth; Berjeaud, Jean-Marc; Rodier, Marie-Hélène; Crépin, Alexandre (Frontiers in Microbiology, 2022)
Altering the gut microbiota can negatively affect the human health. Efforts may be sustained to predict the intended or unintended effects of molecules not naturally produced or expected to be present within the organism on the gut microbiota. Here, culture-dependent and DNA-based approaches were combined to UHPLC-MS/MS analyses in order to investigate the reciprocal interactions between a constructed Human Gut Microbiota Model (HGMM) and molecules including antibiotics, drugs, and xenobiotics. Our HGMM was composed of strains from the five phyla commonly described in human gut microbiota and belonging to Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria, and Actinobacteria. Relevantly, the bacterial diversity was conserved in our constructed human gut model through subcultures. Uneven richness distribution was revealed and the sensitivity of the HGMM was mainly affected by antibiotic exposure rather than by drugs or xenobiotics. Interestingly, the constructed model and the individual cultured strains respond with the same sensitivity to the different molecules. UHPLC-MS/MS analyses revealed the disappearance of some native molecules in the supernatants of the HGMM as well as in those of the individual strains. These results suggest that biotransformation of molecules occurred in presence of our gut microbiota model and the coupled approaches performed on the individual cultures may emphasize on new bacterial strains active in these metabolic processes. From this study, the new HGMM appears as a simple, fast, stable, and inexpensive model for screening the reciprocal interactions between the intestinal microbiota and molecules of interest.